Apoio psicossocial em campos de refugiados : reflexos nos relacionamentos interpessoais - Souza, Beatriz de Barros (2022)
In the world nowadays, about 25 million people are recognized as refugees by some, usually underdeveloped or developing, country. Many of these live in camps or similar arrangements, where it predominates the “humanitarian aid” actions. In recent years, special attention has been devoted to what has been called the “mental health and psychosocial support” (MHPSS) in the various areas of such an aid. In this sense, the thesis investigates the perception of the providers of this support on how it would be reflected on the refugees’ interpersonal relations in such situations. To this end, besides a literary and documentary review on the subject, ten people with some experience of humanitarian aid either in camps, or with refugees in emergencies were interviewed. The episodic interviews were remotely conducted and freely translated by the researcher for a thematic analysis and subsequent discussion in the lights of theoretical contributions by Robert Hinde, in his studies of interpersonal relationships on Social Psychology, and by Axel Honneth in his theory of recognition based on the Hegelian thought and, as such, well-suited to the dialectic thought of interpersonal relationships in Hinde's theory. It is hoped, with this, to provide relevant tools to analyze the ways in which humanitarian aid is provided, as well as its main challenges, in the current times